PROSPECTS Comparative Journal of Curriculum, Learning, and Assessment - Popa, Simona; Marope, P.T.M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Prospects provides comparative and international perspectives on key current issues in curriculum, learning, and assessment. The principal features of the journal are the innovative and critical insights it offers into the equitable provision of quality and relevant education for all; and the cross-disciplinary perspectives it engages, drawing on a range of domains that include culture, development, economics, ethics, gender, inclusion, politics, sociology, sustainability, and education. Prospects aims to influence a wide range of actors in the field of education and development, whether academics, policy-makers, curriculum-developers, assessors, teachers or students. Unlike other journals in the field, which deal only with theoretical or research-related aspects, Prospects also focuses on policy implementation and aims at improving the extent and effectiveness of communication between theorists and researchers, on one side, and policy makers and practitioners, on the other. The journal thus welcomes innovative empirical research, case studies of policy and practice, conceptual analyses and policy evaluations, as well as critical analyses of published research and existing policy. Founded in 1970 and published in English by Springer, Prospects is among the most well-established journals in the field. Editions in Arabic and Mandarin Chinese are available as well. The journal is edited by the International Bureau of Education (IBE), in Geneva. A leading UNESCO Institute and a global center of excellence in curriculum and related matters, the IBE is recognized and valued for the specialist knowledge and expertise that it brings to Member States, promoting new shared global understanding of curriculum, teaching, learning, and assessment.
Keywords: Education; International education; Comparative education; Education, general; International and Comparative Education